ENCLOSED ARE THE ORIGINAL AND THREE (3) COPIES OF A PROPOSAL, PERSONAL EXPOSURE TO ENVIRONMENTAL TOBACCO SMOKE IN COMMERCIAL AIRCRAFT, WHICH I WOULD APPRECIATE THE CENTER FOR INDOOR AIR RESEARCH CONSIDERING FOR FUNDING. (Tufts Archival Research Center, 2007)
Missing Attachments; Letter from Delbert Eatough of the Brigham Young University Department of Chemistry to Charles Nystrom regarding a request for funding from the Center for Indoor Air Research (CIAR) on a study investigating the effect of environmental tobacco smoke (ETS) on airplane passengers.